APOE-ε4 genotype and dementia before and after TIA and stroke: Population-based Cohort Study - Pendlebury, Sarah T (Stroke, 2020)
BACKGROUND AND PURPOSE: APOE-ε4 genotype is a risk factor for sporadic Alzheimer’s disease and reduced recovery from brain injury. Since data on APOE genotype and dementia associated with TIA/stroke are sparse, we determined the associations in a longitudinal population-based cohort. METHODS: All patients with TIA or stroke (2002–2012) in a defined population of 92 728 (Oxford Vascular Study) had follow-up to 5-years. Pre-event and incident post-event dementia were ascertained through direct patient assessment and follow-up, supplemented by review of hospital/primary care records. Associations between pre- and post-event dementia and APOE genotype (ε4/ε4-homozygous and ε4/ε3-heterozygous versus ε3/ε3) were examined using logistic regression and Cox regression models respectively, adjusted for age, sex, education, cerebrovascular burden (stroke severity, prior stroke, white matter disease), diabetes and dysphasia. RESULTS: Among 1767 genotyped patients (mean/SD age=73.0/13.0 years, 901 (51%) male, 602 (34%) TIA), 1058 (59.9%) were APOE-ε3/ε3, 403 (22.8%) were ε4/ε3 and 30 (1.7%) were ε4-homozygous. Homozygosity was associated with both pre-event (adjusted odds ratio (OR)=5.81, 95% CI=1.93-17.48, p=0.002) and post-event dementia (adjusted hazard ratio (HR)=3.64, 1.90-7.00, p<0.0001). Association with post-event dementia was maintained after further adjustment for baseline cognitive impairment (HR=2.41, 1.19-4.89, p=0.01). There were no associations overall between ε4/ε3 and pre-event dementia (adjusted OR=1.47, 0.88-2.45, p=0.14) or post-event dementia (HR=1.11, 0.84-1.48, p=0.47). CONCLUSIONS: In patients with TIA and stroke, APOE-ε4 homozygosity was associated with both pre- and post-event dementia. Associations were independent of cerebrovascular burden, and may be mediated through increased neurodegenerative pathology or vulnerability to injury.